2022
DOI: 10.3390/foods11233847
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Chemical Profile and Antioxidant Activity of Padina pavonica Extracts and Their Application in the Development of Bioactive Chitosan/PLA Bilayer Film

Abstract: Seaweeds are a potentially sustainable source of natural antioxidants that can be used in the food industry and possibly for the development of new sustainable packaging materials with the ability to extend the shelf-life of foods and reduce oxidation. With this in mind, the seasonal variations in the chemical composition and antioxidant activity of brown seaweed (Padina pavonica) extracts were investigated. The highest total phenolic content (TPC) and antioxidant activity (measured by ferric reducing/antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…From tropical to temperate seas, Padina pavonica is extensively distributed because of its accessibility and ecological characteristics [25]. P. pavonica could be used in the production of food [26], and P. pavonica (Linnaeus) brown algae with antioxidant, antibacterial, and anticancer properties, is frequently used in soups, salads, and other foods [27]. Hormophysa cuneiformis has been shown to have a specific phenolic content, antioxidant properties, and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…From tropical to temperate seas, Padina pavonica is extensively distributed because of its accessibility and ecological characteristics [25]. P. pavonica could be used in the production of food [26], and P. pavonica (Linnaeus) brown algae with antioxidant, antibacterial, and anticancer properties, is frequently used in soups, salads, and other foods [27]. Hormophysa cuneiformis has been shown to have a specific phenolic content, antioxidant properties, and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…The extracts from C. spongiosus have been reported to exhibit antioxidant, antibacterial, anticandidal, cytoprotective, insecticidal, and amoebicidal activities [4][5][6][7][8]. It has been previously reported that the bioactivity of the extracts could be affected by the season of algal harvest and extraction method [9][10][11]. However, to our knowledge, no studies on these effects have been performed for C. spongiosus.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, this SI consists of six original research papers [ 1 , 2 , 3 , 4 , 5 , 6 ] and two review papers [ 7 , 8 ] that address recent advances and current knowledge in the proposed field.…”
mentioning
confidence: 99%
“…In addition to the direct addition of algae to various foods, scientists are now also researching the incorporation of bioactive algal extracts into functional food packaging, which can extend the shelf life of foods and ensure greater product safety and quality. In this Special Issue, Čagalj et al [ 6 ] published a paper in which they investigated seasonal variations in the composition and antioxidant activity of the brown alga Padina pavonica . They used microwave-assisted extraction to prepare the extracts.…”
mentioning
confidence: 99%
See 1 more Smart Citation